Analysis of Receivables Management to Control the Risk of Uncollected Receivables at Ayodya Resort Bali - I N T Junarsa; I K Sudiartha; P Subiyanto (Journal of Applied Sciences in Accounting, Finance, and Tax, 2020)
This study aims to determine 1) management of receivables at Ayodya Resort Bali 2) the efforts to control the risk of uncollected receivables at Ayodya Resort Bali. Data used in this study were aging schedules, credit sales, total receivables, credit policy. Measuring instruments used to conduct this research were 5C analysis to analyze credit standards, accounts receivable policy to analyze receivables collection compliance, related ratios to receivables such as accounts receivable turnover ratios, average receivables collection ratios, arrears ratios and billing ratios to assess performance of receivables, a backup method for calculating receivable losses to control the risk of uncollectible receivables. The results of receivables management were classified not good after being analyzed using three indicators. The first indicator is not fulfilled based on the 5C analysis for credit standards. The second indicator is not fulfilled because the collection of accounts receivable is not in correspondence with hotel credit policy. The third indicator is not fulfilled because the results of the analysis on receivable performance using the ratios are not optimal. The amount of receivables is classified high, so it needs to establish an allowance for losses in an effort to control the risk of bad debt.